Розвідкові роботи на території Ходосівського археологічного комплексу - Готун, І.А.; Казимір, О.М. (Археологічні дослідження в Україні, 2009)
The publication is devoted to the results of the archaeological prospecting of the Northern expedition at the Khodosivka archaeological complex. It presents the data on the recently discovered monuments and already known ones with the specified characteristics.